Health and weight - Olaf Hübler (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Many studies have shown that obesity is a serious health problem for our society. Empirical analyses often neglect a number of methodological issues and relevant influences on health. This paper investigates empirically whether neglecting these items leads to systematically different estimates. Based on data from the German Socio-Economic Panel, this study derives the following results. (1) Many combinations of weight and height lead to the same health status. (2) The relationship between health and body mass index is nonlinear. (3) Underweight strengthens individual health and severe obesity has a clear negative impact on health status. Underweight women are more affected than men but obese men are hit harder than women. (4) The hypothesis has to be rejected that weight has an exogenous influence on health. (5) A worse health status is linked with weight fluctuations and deviations between desired and actual working hours. (6) A healthy diet and long but not too long sleeping contribute to a good health status. Moreover, a good parental education and a high parental social status act favorably on health as does personal high income. (7) Four of the big five components of personality, namely openness, extraversion, conscientiousness and agreeableness, contribute to resilience against health problems.
Keywords: 330